WANITA ISLAM DAN CEDAW: ISU-ISU BERKAITAN DENGAN UNDANG-UNDANG KEKELUARGAAN ISLAM DI MALAYSIA: Muslim Women and CEDAW: Issues Related to Islamic Family Law in Malaysia - Noor, Zanariah (Jurnal Syariah, 2023)
The majority of Muslim nations, including Malaysia, ratified the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), with the exception of those provisions that conflict with Islamic teachings, particularly those that deal with Islamic family law. This article discusses conflicting issues that are related to the provisions of Article 16 (1) of CEDAW and Islamic family law in Malaysia such as gender equal rights to marriage, equal rights in divorce-related matters, and equal position between mother and father towards their children. The Islamic family law of Malaysia, the international treaty (CEDAW), and authoritative jurisprudence books as well as contemporary Islamic law texts were all examined as part of this study using a content analysis method. CEDAW’s blanket definition of the discrimination against women and make the same demands disregards of the local and social values of the Malaysian society is inappropriate. The CEDAW’s proposal for amending Islamic family law regarding marriage, divorce and parental rights in Malaysia should not be entertained because it is contradicting with the Islamic and local values uphold by the Malaysian society especially the Muslims.